2015
DOI: 10.1155/2015/650813
|View full text |Cite
|
Sign up to set email alerts
|

Similarity Solution for Free Convection Flow of a Micropolar Fluid under Convective Boundary Condition via Lie Scaling Group Transformations

Abstract: The free convective flow of an incompressible micropolar fluid along permeable vertical plate under the convective boundary condition is investigated. The Lie scaling group of transformations is applied to get the similarity representation for the system of partial differential equations and then the resulting systems of equations are solved using spectral quasi-linearisation method. A quantitative comparison of the numerical results is made with previously published results for special cases and the results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…We assumed, the size of holes in the porous plate plays an important role to simplify the formulation of the boundary conditions. By taking the aforesaid assumptions into consideration the governing boundary layer equations with corresponding boundary conditions for steady convective flow are as follows: ux+vy=0,uux+vuy=μ+kρ2uy2+gβTfalse(TTfalse)cosα+gβcfalse(CCfalse)cosα+kρNy,uNx+vNy=γρj2Ny2kρjuy+2N,uTx+vTy=κρCp2T…”
Section: Reactive Radiative Micropolar Thermo‐solutal Modelmentioning
confidence: 93%
“…We assumed, the size of holes in the porous plate plays an important role to simplify the formulation of the boundary conditions. By taking the aforesaid assumptions into consideration the governing boundary layer equations with corresponding boundary conditions for steady convective flow are as follows: ux+vy=0,uux+vuy=μ+kρ2uy2+gβTfalse(TTfalse)cosα+gβcfalse(CCfalse)cosα+kρNy,uNx+vNy=γρj2Ny2kρjuy+2N,uTx+vTy=κρCp2T…”
Section: Reactive Radiative Micropolar Thermo‐solutal Modelmentioning
confidence: 93%
“…The values in (16) are used in the recurrence relations (11)- (15) and 1 , 2 , 3 , 4 , 5 , and 6 are calculated such that they satisfy the boundary conditions at = 1; then we obtain nondimensional velocity components, temperature distribution, and concentration for various parameters by substituting these constants into the respective Taylor series.…”
Section: Re Pr Cosmentioning
confidence: 99%
“…Yao et al [15] analyzed an incompressible laminar viscous fluid flow and heat transfer over a stretching/shrinking sheet with convective boundary conditions and have found that the convective boundary condition results in a temperature slip at the wall. RamReddy et al [16] studied an incompressible laminar free convective micropolar fluid flow along a permeable vertical plate with the convective boundary condition and obtained a numerical solution using spectral quasilinearization method. Postelnicu [17] examined the effects of Soret and Dufour on a two-dimensional steady stagnation point flow of a free convective Darcian fluid with suction/injection and the governing partial differential equations are reduced to nonlinear ordinary differential equations using similarity transformations and then solved by the Keller box method.…”
Section: Introductionmentioning
confidence: 99%
“…(Chamka et al, 2014) studied the effects of viscous dissipation and magnetic field on free convection flow in a non Darcy porous medium saturated with a nanofluid under convective boundary condition. (RamReddy et al, 2015) analyzed the similarity solution of free convection flow of an incompressible micropolar fluid with convective boundary condition using lie group transformations. investigated the influence of convective boundary condition on MHD mixed convection flow of micropolar fluid towards nonlinear stretched sheet.…”
Section: Introductionmentioning
confidence: 99%